Pengaruh Model Pembelajaran Accelerated Learning Included by Discovery (ALID) terhadap Hasil Belajar Kognitif Peserta Didik - Wiranti Wiranti; Safei Safei; Jamilah Jamilah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Accelerated learning Included by Discovery (ALID) learning model is a learning model that aims to create constructivist and humanistic learning, namely learning that provides opportunities for students to find concepts and solve problems with the full potential of students so that learning is more meaningful. This study aims (1) to determine the learning outcomes of class VIII students in science subjects taught by applying the ALID learning model at SMPN 8 Bulukumba (2) to determine the learning outcomes of class VIII students in science subjects taught without applying learning models ALID at SMPN 8 Bulukumba (3) to determine the effect of the ALID learning model on the learning outcomes of class VIII students in science subjects at SMPN 8 Bulukumba. The type of research applied in this study is a quasi-experimental type. The researchdesign used was a non-equivalent control group design. The sample in this study were 20 class VIII A students who were selected as the experimental class and class VIII B as the control class. The instrument used is a cognitive learning outcome test of 15 numbers related to the material of the digestive system. The data analysis technique used is descriptive statistical analysis and inferential statistics. The results showed that students who were taught by applying the Accelerated Learning Included by Discovery (ALID) learning model had an average learning outcome of 72.25. Meanwhile, students who are taught by applying conventional learning models have an average learning outcome of 52.6. The results of inferential statistical analysis obtained a sign value for learning outcomes of 0.000, this value indicates that the sign < = 0.00 <0.05 so that H0 is rejected and H1 is accepted. Based on the results of the analysis, it can be concluded that the application of the Accelerated Learning Included by Discovery (ALID) learning model affects the cognitive learning outcomes of class VIII students in science subjects at SMPN 8 Bulukumba.